2006
DOI: 10.1177/159101990601200207
|View full text |Cite
|
Sign up to set email alerts
|

Heparin or Local Thrombolysis in the Management of Cerebral Venous Sinus Thrombosis?

Abstract: Patients with acute cerebral venous sinus thrombosis treated with Heparin or in situ thrombolysis in our department were evaluated in an attempt to rationalize treatment with heparin or thrombolysis. 279 patients with angiographically proven acute cerebral venous sinus thrombosis were included in the study. Patients were classified into mild and severe clinical grade. The study was divided into three phases. Phase I included 27 patients treated with systemic heparin. Phase II included 72 patients, 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Hence, there are no proven treatment guidelines. However, according to a retrospective review, the mortality rate for patients treated with either IV heparin or local thrombolytics was 13% compared with 48% in untreated patients 12 and local thrombolysis has better follow-up results in severe cases 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, there are no proven treatment guidelines. However, according to a retrospective review, the mortality rate for patients treated with either IV heparin or local thrombolytics was 13% compared with 48% in untreated patients 12 and local thrombolysis has better follow-up results in severe cases 15 .…”
Section: Resultsmentioning
confidence: 99%
“…All patients had proven CVT with cerebral hemorrhagic venous infarcts. The grading of CVT was done using the criteria proposed by INR, King Edward Memorial Hospital (KEM), Mumbai, India: [10] Six patients with clinical Grade 3, two with Grade 4, and two with Grade 5 [ Table 1]. …”
Section: Resultsmentioning
confidence: 99%
“…Among our patients, one patient died and was related to the disease and not to thrombolytic therapy. [10] Intravenous thrombolysis is associated with variable outcomes, as the concentration of the thrombolytic agent delivered at the site of occlusion is low. Thrombolysis is accelerated through direct intrasinus infusion of the thrombolytic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Complete and partial recanalization was seen in 87% and 6% respectively, whereas 8% of the patients showed no recanalization. At discharge, only 3 patients had a poor mRS (3)(4)(5), whereas 45 had an excellent clinical outcome of mRS (0-2). Six patients died despite receiving aggressive treatment.…”
Section: Endovascular Mechanical Thrombectomymentioning
confidence: 98%
“…This study showed the efficacy and safety of IST in patients with severe clinical symptoms and no added benefit in those with mild clinical symptoms. 5 In a small prospective study by Garge and colleagues, 6 10 patients underwent IST; 9 of them had a good clinical outcome (mRS ≤ 2), and only 1 patient did not respond to local thrombolysis and succumbed to intracranial hemorrhagic infarct within 48 hours.…”
Section: Intrasinus Thrombolysismentioning
confidence: 99%